Cultural diversity in the news media: a democratic or a commercial need? - Awad Cherit, Isabel (Javnost-The Public, 2008)
This paper distinguishes between laissez-faire and interventionist models used to justify and implement cultural diversity initiatives in the news media. The laissez-faire model is characteristic of U.S journalism. However, due to the convergence of media systems and the widespread adoption of diversity management, the laissez-fair model may also become the prevalent model throughout other Western democracies, in Europe and elsewhere. The paper argues that the problem with the laissez-fair approach to cultural diversity in the media is that it relies on commercial instead of normative justifi cations. As a result, cultural diversity is mostly reduced to ornament. Equated with accuracy and treated as a business asset, diversity serves, rather than challenges, the existing media system. By failing to open suffi cient spaces for alternative social voices, business-driven media policies do not respond to the democratic needs of a multicultural society.